Improved glucose biosensor based on glucose oxidase-horseradish peroxidase/multiporous tin oxide modified-electrode - A. K. M., Kafi; Samiul, Alim; Rajan, Jose; M. M., Yusoff; Jaya Vejayan, Palliah (Universiti Malaysia Pahang, 2018)
The fabrication of a crosslinked network of glucose oxidase-horseradish peroxidase/tin oxide (GOx-HRP/SnO2), immobilized on glassy carbon electrode (GCE) and its utilization as a sensor for glucose detection has been reported. The 3-D network established with GOx-HRP/SnO2 has possessed high sensitivity and stability by performing the electrocatalytic features in sensing of glucose. The turbidity of fabrication has been scanned and analyzed using UV-Vis Spectroscopy. The morphology and composition of the fabricated GOx-HRP modified multi-nanoporous SnO2 nanofibers were characterized by scanning electron microscopy (SEM). Cyclic voltammetry and amperometry were used to study the proposed electrochemical biosensor. The effect of applied electrode potential, pH and the concentration of glucose on the sensitivity of the biosensor have been systemically investigated which indicates that these systems should be very useful for other sensing applications.